Pengaruh Kegunaan yang Dirasakan Dari Ulasan Online, Nilai Emosional, Risiko yang Dirasakan dan Kepercayaan Terhadap Minat Beli Pada Aplikasi TikTok Shop. - Pratama, Raden Sigit Surya; Astuti, Budi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to examine how perceptions of the usefulness of online reviews, emotional value, perceived risk, and trust influence consumers' purchase intentions. A quantitative research approach was employed, involving 200 respondents from the Special Region of Yogyakarta who are active TikTok users and show interest in shopping through TikTok Shop. Data were analyzed statistically using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The findings reveal that: 1) Perceived usefulness of online reviews has a significant and positive impact on trust and purchase intention, 2) Trust plays a crucial role in enhancing purchase intention and reducing perceived risk, 3) Emotional value positively influences both trust and the intention to purchase, and 4) Perceived risk also affects consumers' buying decisions. This research contributes to a deeper understanding of the factors that shape consumer purchase intention, particularly in the context of online reviews and emotional value